2022
DOI: 10.1111/bcpt.13728
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity and therapeutic drug monitoring of polyglutamates of methotrexate after daily or weekly administration of low‐dose methotrexate in patients recently diagnosed with rheumatoid arthritis

Abstract: Low‐dose methotrexate can be challenging to treat rheumatoid arthritis due to side effects, lack of adherence and risk of medication errors. The aim of this study was to explore the safety and efficacy of low‐dose methotrexate administered daily or weekly in patients with rheumatoid arthritis. Patients were randomized according to a total oral dose of 12.5 mg of methotrexate administered: (A) divided in 5 days/week and (B) once per week. Patients were assessed along 24 weeks after starting treatment. Polygluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
1
0
1
Order By: Relevance
“…Recently, a randomized controlled study showed that daily therapy is as effective as weekly therapy when the polyglutamate-3 levels are similar. This study also showed that obese patients achieve a lower concentration of Mtx-PG3 ( 125 ). Clinical response in several other diseases like juvenile rheumatoid arthritis, juvenile dermatomyositis, and inflammatory bowel disease was also reported to be affected by the Mtx-PG concentrations.…”
Section: Methotrexatesupporting
confidence: 61%
“…Recently, a randomized controlled study showed that daily therapy is as effective as weekly therapy when the polyglutamate-3 levels are similar. This study also showed that obese patients achieve a lower concentration of Mtx-PG3 ( 125 ). Clinical response in several other diseases like juvenile rheumatoid arthritis, juvenile dermatomyositis, and inflammatory bowel disease was also reported to be affected by the Mtx-PG concentrations.…”
Section: Methotrexatesupporting
confidence: 61%
“…In those patients with low MTX‐PG 3 levels (mostly younger patients in our cohort (data not shown)) despite treatment with a maximal dosage of 25 mg/week MTX SC, alternative approaches to MTX administration are currently being explored. These include daily rather than weekly dosing schemes (5 days per week, divided weekly dose), 28 pH‐sensitive and colon‐specific nanoparticles loaded with MTX to target the gut specifically, 29 and addition of PK enhancers to MTX, such as efflux transporter blockers (MTX Forte, Amplio Pharma, Sweden). Further research is necessary to evaluate the added value of these new MTX administration strategies.…”
Section: Discussionmentioning
confidence: 99%
“…1 finden sich Angaben zu bDMARD, bei denen dies beschrieben wurde. Auch bei MTX ist ein therapeutisches "Drug-Monitoring" möglich [54]. Unzureichende (und auch deutlich zu hohe) Medikamentenspiegel können durch interagierende Medikamente, neutralisierende Antikörper, v. a. aber durch "Non-Compliance", verursacht werden.…”
Section: Ursachen Eines Therapierefraktären Verlaufesunclassified